Wafer-scale monodomain films of spontaneously aligned single-walled carbon nanotubes - He, Xiaowei; Gao, Weilu; Xie, Lijuan; Li, Bo; Zhang, Qi; Lei, Sidong; Robinson, John M.; Hároz, Erik H.; Doorn, Stephen K.; Wang, Weipeng; Vajtai, Robert; Ajayan, Pulickel M.; et al. (Nature nanotechnology, 2016)
The one-dimensional character of electrons, phonons and excitons in individual single-walled carbon nanotubes leads to extremely anisotropic electronic, thermal and optical properties. However, despite significant efforts to develop ways to produce large-scale architectures of aligned nanotubes, macroscopic manifestations of such properties remain limited. Here, we show that large (>cm 2 ) monodomain films of aligned single-walled carbon nanotubes can be prepared using slow vacuum filtration. The produced films are globally aligned within ±1.5° (a nematic order parameter of ∼1) and are highly packed, containing 1 × 10 6 nanotubes in a cross-sectional area of 1 μm 2 . The method works for nanotubes synthesized by various methods, and film thickness is controllable from a few nanometres to ∼100 nm. We use the approach to create ideal polarizers in the terahertz frequency range and, by combining the method with recently developed sorting techniques, highly aligned and chirality-enriched nanotube thin-film devices. Semiconductor-enriched devices exhibit polarized light emission and polarization-dependent photocurrent, as well as anisotropic conductivities and transistor action with high on/off ratios. Large films of aligned and closely packed single-walled carbon nanotubes can be prepared through slow vacuum filtration, and used to create terahertz polarizers, thin-film transistors, polarized light emission devices, and polarization-sensitive detectors.